Justice as a Meta Value of Corrective Justice in Providing Restitution for Unjust Enrichment: A Study on Rules, Norms, Principles, and Foundation - Faizal Kurniawan; Prawitra Thalib; M. Hadi Subhan; Bart Jansen; Zuhairah Ariff Binti Abd Ghadas (Jurnal Hukum, 2023)
The legal foundation is one of the most important sources of law that has been emphasized in several legal theories. However, concepts regarding legal foundation are still heavily debated and intertwined with other legal principles, legal values, legal norms, legal theorems, and legal rules. Foundation, principles, and norms are general concepts discussed in the law field as a separate point of discussion in the study of law, especially in legal theory.This showcases that the knowledge regarding concepts and the standing of different principles, values, norms, and rules are important in studying a particular field of law. However, in practice, most legal scholars and professors in the field of law are still unaware of such concepts that often overlap with one another. Generally, foundations are meta values from principles, principles are the meta values of norms, and norms are meta values of a rule. In comparison, values are the equivalent of principles and fundamental values. A theorem is the equivalent of a norm, which is embodied in a rule, and the rule itself is the most concrete implementation of a principle, which may be in the form of a written or unwritten rule. This paper aims to explore the relationship between justice, corrective justice, restitution, and unjust enrichment. It will discuss how fundamental values, principles, and norms serve as meta-values in achieving justice. Additionally, it will examine the role of corrective justice in providing restitution for cases of unjust enrichment.